The role of oxytocin in familiarization-habituation responses to social novelty - Tops, Mattie; Huffmeijer, Renske; Linting, Mariëlle; Grewen, Karen; Light, Kathleen; Koole, Sander; Bakermans-Kranenburg, Marian; IJzendoorn, Marinus (Frontiers in Psychology, 2013)
Stress or arousal responses to novel social contexts ease off when individuals get familiar with the social context. In the present study we investigated whether oxytocin is involved in this process of familiarization-habituation, as oxytocin is known to increase trust and decrease anxiety. Fifty-nine healthy female subjects took part in the same experimental procedure in two sessions separated by four weeks. In the first (novelty) session state trust scores were significantly positively correlated with salivary oxytocin levels, while in the second (familiarity) session state trust scores were significantly negatively correlated with salivary oxytocin levels. In a path model, oxytocin was associated with increased trust in the novelty session and trust was associated with decreased oxytocin levels in the familiarity session. The results are consistent with the idea that oxytocin decreases stress-to-novelty responses by promoting familiarization to novel social contexts.